A review and meta-analysis of prospective studies of red and processed meat, meat cooking methods, heme iron, heterocyclic amines and prostate cancer. Issue 1 (December 2015) - Bylsma, Lauren; Alexander, Dominik
Abstract Prostate cancer remains a significant public health concern among men in the U.S. and worldwide. Epidemiologic studies have generally produced inconclusive results for dietary risk factors for prostate cancer, including consumption of red and processed meats. We aimed to update a previous meta-analysis of prospective cohorts of red and processed meats and prostate cancer with the inclusion of new and updated cohort studies, as well as evaluate meat cooking methods, heme iron, and heterocyclic amine (HCA) intake exposure data. A comprehensive literature search was performed and 26 publications from 19 different cohort studies were included. Random effects models were used to calculate summary relative risk estimates (SRREs) for high vs. low exposure categories. Additionally, meta-regression analyses and stratified intake analyses were conducted to evaluate dose-response relationships. The SRREs for total prostate cancer and total red meat consumption, fresh red meat consumption, and processed meat consumption were 1.02 (95 % CI: 0.92–1.12), 1.06 (95 % CI: 0.97–1.16), and 1.05 (95 % CI: 1.01–1.10), respectively. Analyses were also conducted for the outcomes of non-advanced, advanced, and fatal prostate cancer when sufficient data were available, but these analyses did not produce significant results. No significant SRREs were observed for any of the meat cooking methods, HCA, or heme iron analyses. Dose-response analyses did not reveal significant patterns of associations between red or processed meat and prostate cancer. In conclusion, the results from our analyses do not support an association between red meat or processed consumption and prostate cancer, although we observed a weak positive summary estimate for processed meats.